Integrating social and environmental sustainability into the operations of a multinational gold mining company: A case study of AngloGold Ashanti - Hollesen, Paul Michael (GSB: Faculty, 2016)
Integrating social and environmental sustainability into the operations of a multinational mining company is increasingly important to its long term viability. Yet, the boundaries of what constitutes responsible social and environmental sustainability practices are contested with stakeholder governance expectations continuing to evolve, grow, and at times conflict. AngloGold Ashanti needs to navigate the complex terrain between its commitment to maximise returns delivered to shareholders, juxtaposed with those of respecting the environment, and communities being better off for the company having been there. The dissertation includes a meta-synthesis of primary research undertaken over some five years and examines AngloGold Ashanti's social and environmental sustainability integration efforts from the perspective of a head office role, a critical realist ontology and grounded theory epistemology. A mid-range grounded theory and CIMO design proposition argue for interventions that trigger mechanisms fostering mutual meaning between stakeholders regarding social and environmental sustainability and its integration, through a process of continual improvement, into company strategy, management structures (incorporating role clarity and functional capability), systems and processes. Out of which come locally rooted, internationally defensible operational practices with the intended outcomes of internalising costs and externalising benefits arising from exploration and mining, therein seeking to meet stakeholder governance expectations.